The chronic myelocytic cell line K562 contains a breakpoint in bcr and produces a chimeric bcr/c-abl transcript. - Grosveld, G (1986)
In the DNAs of all Ph1-positive chronic myelocytic leukemia patients studied to date, a breakpoint on chromosome 22 (the Ph1 chromosome) can be demonstrated with a probe from the bcr (breakpoint cluster region). Although the K562 cell line was established from cells of a chronic myelocytic leukemia patient, we have been unable to detect the Ph1 chromosome by cytogenetic means. Employing a probe from the 5' region of bcr, we have cloned an amplified Ph1 breakpoint fragment from K562. This demonstrates that K562 contains multiple remnants of a Ph1 chromosome with a breakpoint within bcr and thus may serve as a model system for the study of Ph1-positive chronic myelocytic leukemia at a molecular level. The isolation of bcr cDNA sequences shows that parts of bcr encode a protein. Employing K562, we demonstrate the presence of an abnormally sized mRNA species hybridizing to c-abl and to a bcr cDNA probe, indicating the possible consequence of the Ph1 translocation on a transcriptional level in chronic myelocytic leukemia. The isolation and sequencing of a cDNA containing the breakpoint area of this mRNA provide further evidence for its chimeric structure. Cloning of large stretches of chromosomal DNA flanking bcr and c-abl sequences in K562 and identification of the exons participating in the formation of the chimeric mRNA shows that a splice of at least 99 kilobases is made to fuse the 3' bcr exon to the 5' c-abl exon. Furthermore two chimeric cDNAs were isolated containing chromosome 9 sequences that map 43.5 kilobases downstream from the K562 breakpoint. These chromosome 9 sequences neither hybridize to the 8.5-kilobase chimeric c-abl mRNA nor to normal c-abl mRNAs in Hela cells and probably represent incorrect splicing products present in the K562 cell line.